ICU sedation with dexmedetomidine after severe traumatic brain injury. (23rd August 2016) - Humble, Stephen S.; Wilson, Laura D.; Leath, Taylor C.; Marshall, Matthew D.; Sun, Daniel Z.; Pandharipande, Pratik P.; Patel, Mayur B.
Abstract: Objective : To comprehensively describe the use of dexmedetomidine in a single institutional series of adult ICU patients with severe TBI. This study describes the dexmedetomidine dosage and infusion times, as well as the physiological parameters, neurological status and daily narcotic requirements before, during and after dexmedetomidine infusion. Methods : This study identified 85 adult patients with severe TBI who received dexmedetomidine infusions in the Trauma ICU at Vanderbilt University Medical Center between 2006–2010. Demographic, haemodynamic, narcotic use and sedative use data were systematically obtained from the medical record and analysed for changes associated with dexmedetomidine infusion. Results : During infusion with dexmedetomidine, narcotic and sedative use decreased significantly ( p < 0.001 and p < 0.05). Median MAP, SBP, DBP and HR also decreased significantly during infusion when compared to pre-infusion values ( p < 0.001). Despite the use of dexmedetomidine, RASS and GCS scores improved from pre-infusion to infusion time periods. Conclusions : The findings demonstrate that initiation of dexmedetomidine infusion is not associated with a decline in neurological functioning in adults with severe TBI. Although there was an observed decrease in haemodynamic parameters during infusion with dexmedetomidine, the change was not clinically significant and the requirements for narcotics and additional sedatives were minimized.